Assessing the Economic Value of Public Service Broadcasting in Taiwan Using the Contingent Valuation Approach - Lin, Yih-Ming; Fu, Tsu-Tan; Yeh, Powen; Huang, Mei-Ying (Journal of media economics, 2013)
The objective of the study is to provide empirical evidence on the value of public service broadcasting (PSB) in Taiwan, which is a critical factor when considering the provision of more public funding. Being based on a nationwide telephone survey in Taiwan, this study uses the contingent valuation method to elicit citizens' willingness to pay (WTP) for maintaining the current PSB in Taiwan. The results show that household average WTP per year for PSB is estimated to be NT$982 (US$29.89), which is equal to 0.18% of GDP per capita in 2007. Such WTP estimate is much higher than the current government subsidy for PSB per household, which implies respondents' high appreciation on PSB as well as the potential benefit that Taiwan PSB could bring to the family. Our estimates of WTP provide important information for government authorities and policy-makers when making funding decisions. Furthermore, our survey results also point to some prioritized functions as potential niches on which the Taiwan PSB could focus in the future.